Optimization of process parameters for the enhanced production of fibrinolytic enzyme by a newly isolated marine bacterium. (September 2020) - Anusree, M.; Swapna, K.; Aguilar, C.N.; Sabu, A.
Abstract: Thrombotic disorders are the major cause of death worldwide. As the thrombolytic agents we use today were having lot of side effects, microbial enzymes, which have marked specificity to fibrin, gain attention. A marine bacterium with potent fibrinolytic activity was successfully isolated and identified as Serratia rubidaea KUAS001. Process parameters for the enhanced production of the enzyme under submerged fermentation were optimized. It includes, incubation time (48 h), inoculum size (0.8% v/v ), pH (6.0), temperature (30 °C) and concentration of nutrient sources like maltose (1.5% w/v ), yeast extract (1.5% w/v ), NaCl (1.5% w/v ) and skimmed milk powder (0.15% w/v ). Enhanced fibrinolytic enzyme activity (394.9 IU/ml) was obtained after optimization, which is 2.57 times higher than the same under unoptimized conditions. Highlights: Fibrinolytic enzyme yielding marine bacterium Serratia rubidaea KUAS001was isolated. Optimization of process parameters were performed using one factor at a time method. Under optimized conditions enhanced enzyme activity of 394.9 IU/ml was obtained. A 2.57 fold increase in enzyme yield compared to unoptimized conditions is reported.